Modeling the response of crop emergence to sowing depth and soil water deficit in direct-seeded rice - Kanno, Noriko; Kumar, Virender; Kato, Yoichiro (Springer, 2025)
Background and aims Dry direct seeding of rice in the tropics often suffers from poor crop establishment owing to soil water deficit. A potential solution is sowing deeply to utilize residual soil moisture farther below the surface. We evaluated rice emergence under various sowing depths and soil moisture conditions and tested a model framework of it as a simultaneous function of sowing depth and soil moisture.